AB0032 Toll-like receptor stimulation induces tolerizable and non-tolerizable effects in rheumatoid arthritis synovial fibroblasts. (23rd January 2014) - Klein, K.; Gay, R. E.; Michel, B.; Lin, L.-L.; Gay, S.; Ospelt, C.
Abstract : Background: Activation of the innate immune system via Toll-like receptors (TLRs) is considered to play an important role in the propagation of the inflammatory response in rheumatoid arthritis (RA) patients. In macrophages, repeated stimulation of TLR pathways with LPS leads to a tolerant state of the cell, protecting inflamed tissues from inflammation-induced damage. We hypothesized that a lack of tolerizable effects in stromal cells significantly contributes to sustained inflammation and inflammation-induced damage seen in RA. Objectives: To investigate tolerizable and non-tolerizable effects in RA synovial fibroblasts (RASF) after TLR stimulation compared to macrophages. Methods: RASF and in vitro differentiated peripheral blood derived macrophages from healthy donors were treated with the TLR4 agonist LPS (100 ng/ml). 24h after the initial stimulation, cells were washed and re-stimulated with 1/10 of the initial LPS concentration for another 24h. Supernatants were collected from the second treatment period for ELISA and cells were harvested for isolation of RNA or protein extracts after a total treatment period of 48h. The expression of different genes, including cytokines and chemokines (IL6, CCL5, IL33, TNFSF15, CXCL10), matrix metalloproteinases (MMP1, MMP3, MMP13), receptors (TLR2, TLR3, TLR4, MDA5, RIG1) as well as signaling molecules, activators and inhibitors of the TLR pathway (SHIP1, SOCS1, TNFAIP3, OAS1) was analyzed by quantitative Real-time PCR, Western blotting and ELISA. The expression levels of interferon regulatory factor 3 (IRF3) and interleukin-1 receptor-associated kinase 4 (IRAK4) were analyzed by Western blotting. Results: As expected, the expression of IL6 decreased in double-stimulated (886 ± 596 pg/ml) compared to single-stimulated (2368 ± 315 pg/ml; p<0.01) macrophages (n=4). On the other hand, RASF (n=10) maintained their production of IL6 after repeated TLR4 stimulation and secreted 13237 ± 5764 pg/ml IL6 after a single LPS stimulation and 12421 ± 7178 pg/ml IL6 after double stimulation. A lack of tolerizable effects after LPS stimulation of RASF was also found for MMP1, MMP3, MMP13, CCL5, IL33, TLR3 and TNFAIP3. Interestingly, the known interferon-responsive genes OAS1, RIG1, MDA5 and CXCL10 were tolerizable not only in macrophages but also in RASF. RASF (n=5) secreted 531 ± 385 pg/ml CXCL10 after a single LPS stimulation and 111 ± 97 pg/ml CXCL10 after double stimulation (p<0.05). TLR4 mRNA was not changed in macrophages or in RASF by LPS double stimulation suggesting that a change of TLR4 expression itself was not responsible for the tolerizable effects. Expression levels of IRF3 and IRAK4 were similar in single and double stimulated RASF, excluding expression changes in these signaling molecules as the underlying mechanism for tolerizable effects. Conclusions: Interferon-responsive genes are tolerizable not only in macrophages but also in RASF after LPS stimulation. However, since many pro-inflammatory cytokines and matrix metalloproteinases are non -tolerizable genes in RASF, we conclude that the lack of tolerization in these cells keeps them aggressive in persistent inflammation. Acknowledgements: IMI-BT Cure (Pfizer), IAR Disclosure of Interest: K. Klein Grant/research support from: IMI-BTCure (Pfizer), IAR, R. Gay Grant/research support from: IMI-BTCure (Pfizer), IAR, B. Michel: None Declared, L.-L. Lin Employee of: Pfizer, S. Gay Grant/research support from: IMI-BTCure (Pfizer), IAR, C. Ospelt Grant/research support from: IMI-BTCure (Pfizer), IAR